Classification of Streptomyces Spore Surfaces into Five Groups - Dietz, Alma (1971)
Streptomyces spores surfaces have been classified into five groups, smooth, warty, spiny, hairy, and rugose, by examination of carbon replicas of spores with the transmission electron microscope and by direct examination of spores with the scanning electron microscope.